Surgical management of orthopedic problems in adult patients with cerebral palsy [Beyin felçli erişkin hastalardaki ortopedik sorunlarin cerrahi tedavisi.] - (:unkn) unknown (My University, 2005)
OBJECTIVES: We evaluated the results of surgical treatment for orthopedic problems in adult patients with cerebral palsy. METHODS: Nine adult patients with cerebral palsy (4 females, 5 males; mean age 22 years; range 19 to 29 years) were managed surgically to lessen pain, correct deformities and contractures, and enhance their mobilization potential. Seven patients underwent bilateral multiple-level tendinous and/or musculotendinous release procedures involving the lower extremities, of whom two patients underwent additional triple arthrodesis, and one patient underwent extension osteotomy in the knee. One patient was treated with proximal femoral and distal tibial derotation osteotomies and bilateral hamstring release for knee flexion contractures. Finally, one patient was treated with posterior fusion with instrumentation for thoracolumbar scoliosis. Before surgery, four patients were community ambulators, and one patient could walk only with the aid of bilateral crutches. Four patients with total body involvement could not walk, but they could sit without support except for one patient with scoliosis. The mean follow-up was 25 months (range 8 to 49 months). RESULTS: On final evaluations, eight patients could walk without support, and one patient who could not sit preoperatively managed to sit without support. Three patients developed bilateral, five patients developed unilateral superficial skin wounds at the back of the heels associated with cast/brace use, and deep wound infection was encountered in the patient with scoliosis. All the wounds healed with early debridements and antibiotic therapy, together with the modifications made in cast/brace applications, without the need for implant removal. CONCLUSION: Surgical treatment of orthopedic problems in adult patients with cerebral palsy is of substantial importance in enhancing their sitting and walking capacities, and in restoring their community-based relations and activities.